Student Teams-Achievement Division (STAD) To Increase Students' Social and Spiritual Intelligence - Das, St. Wardah Hanafie; Halik, Abdul; Naim, Muhammad; Musakkir, Musakkir; Mahsan, Syaiful; T, Syamsu (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research discusses STAD in Cooperative Learning strategy to enhance students' social intelligence. It focuses on how to apply the cooperative learning strategy, social intelligence, strengths, and weaknesses, which aims to determine the process of implementing the unified learning model from beginning to end and describe the social intelligence of students after its implementation. The author used classroom action research with a qualitative descriptive approach to complement this study. Research on the disclosure of problems as they existed was data analysis using field research, observation, interviews, and documentation using data analysis, namely, data presentation, data reduction, and withdrawal. The results of this study indicated that the implementation of PAI learning on the STAD-type cooperative learning strategy in SMPN 4 Simbang class VII-A was well-implemented, effective, efficient, fun, and exciting. Besides, it had a positive impact on students ' learning. There were several advantages to implementing cooperative learning strategies, including fun, self-confidence, responsibility, interest in Education, and creative thinking. Some of these factors were interconnected or related, needed, and complemented each other. Then, the shortcomings in implementing cooperative learning strategies included excessive pleasure, less skill, and limited learning resources and media.